EVEKTIFITAS GADGET/AI DALAM PROSES BELAJAR - Ainun; Sri Yunita Taligansing; Pendriyanto; Chika; Moh. Iqra; Sartin (JIP: Jurnal Ilmu Pendidikan, 2026)
The rapid advancement of digital technology has transformed the educational landscape, with gadgets and Artificial Intelligence (AI) now becoming an integral part of students' learning activities. This study aims to investigate the effectiveness of integrating gadgets and AI-based tools in enhancing learning outcomes, motivation, and student autonomy in the learning process. Utilizing a systematic literature review and a descriptive quantitative approach, data were gathered from questionnaires distributed to a sample of students and educators, alongside an analysis of relevant prior research. The findings indicate that the utilization of AI (such as educational chatbots, adaptive learning platforms, and automated summarization tools) and gadgets significantly improves information accessibility and personalizes learning according to individual pacing. However, this effectiveness highly depends on the users' digital literacy levels and students' self-regulation to avoid digital distractions. This study concludes that AI and gadgets hold immense potential as learning accelerators when balanced with proper pedagogical supervision and clear ethical guidelines.